Effect of pH on Adsorption of Lead(II) Using Syzygium Jambos - P. Srisha,; Sultana , Sayeeda (International Journal of Psychosocial Rehabilitation, 2020)
The industrialization and modernization all over the world causes environmental imbalances throughtheir byproducts of heavy metals, these are becoming dangerous to the health of human beings, animals and aquatic creatures. The heavy metals can enter a water supply by industrial and consumer waste and thereby releasing heavy metals into streams, lakes, rivers, and groundwater. Lead (Pb) is one of the heavy metals, it becoming a part of our day to day life through various applications. This paper proposes Syzygium Jambos(SJ) as an adsorbent for the removal of Lead(II) from aqueous solutions. The metal ions mostly dependent on the pH of the aqueous solution, we investigated the effect of pH.The atomic absorption spectroscopy (AAS) is used to determine the amount of adsorption at various pH values. The optimal pH value found as 2.0 for 76.5% of maximum adsorption of Lead(II) using Syzygium Jambos. The detailed research review indicated that very less research happened in the utilization of Syzygium Jambos.Therefore the results presented in this paper are novel and are useful for the society to sidestep the toxicity of Lead(II).